Understanding What Drives Youth Interest in Agribusiness Jobs: A Study from Dukuh Dempok Village - Rojabi, Muhammad Noval; Muksin (Jurnal Manajemen Agribisnis dan Agroindustri, 2024)
Based on field observations conducted in Dukuh Dempok Village, Wuluhan District, Jember Regency, only about 20% of young people express interest in working in agriculture. This indicates a lack of interest among youth in agricultural professions, particularly in Dukuh Dempok Village. This study aims to analyze the characteristics of agribusiness jobs that appeal to young people in the area. The method used in this study is a survey approach. Sampling was conducted using probability sampling techniques, specifically proportionate stratified random sampling. The analysis involved examining various internal variables such as formal education, age, perception of parental background, and perception of farming efforts, along with external factors including social environment, the role of extension workers, and facilities and infrastructure. The data was converted into interval data using the Mean Score Index (MSI) and was then tested for validity, reliability, and classical assumptions with the assistance of SPSS 25 software. The data analysis employed a quantitative descriptive method, specifically multiple linear regression tests using SPSS. Hypothesis testing was performed using the t-test and F-test. The results of the study indicated that both internal and external factors significantly influence young people's interest in pursuing careers in the agribusiness sector.